PENGARUH PROFESIONALISME, PENGALAMAN DAN DISIPLIN TERHADAP KINERJA PEGAWAI KANTOR KEMENTERIAN AGAMA KABUPATEN PROBOLINGGO - jurnalmap map; Evi Fransiska; Soenarmi ÔÇì (MAP (Jurnal Manajemen dan Administrasi Publik), 2019)
ABSTRACT This study aims to study professionalism, experience and discipline on the performance of employees of the Office of the Ministry of Religion, Probolinggo Regency. The population in this study were 50 employees in the Office of the Ministry of Religion of Probolinggo Regency. To evaluate the proposed hypothesis used the F test and the T Test and to study the valued contribution of the variable to the dominant analysis. The results of simultaneous analysis of professionalism, experience and discipline on employee performance at the Office of the Ministry of Religion of Probolinggo Regency. This asks for the calculated F value of 259,554 and has a significance of less than 0.05. Likewise the results of the partial analysis show that the variables of professionalism, work experience and discipline each have a significant effect on the performance of employees of the Ministry of Religion Office in Probolinggo Regency because the value of t counted to three variables will be greater than the value of t table and significant values ÔÇïÔÇïless than 0, 05. Keywords: professionalism, experience, discipline, performance